Evaluating the Bioactivity and Antimicrobial Efficacy of Advanced Restorative Materials - Kashif Adnan, Waqas Ahmad Farooqi, Azeem Hussain Soomro, Asia Noureen, Hafiz Mahmood Azam, Ashar Hussain, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This research was aimed at providing a general perspective on how advanced restorativematerials can be used in practice, with particular reference to their perceived bioactivity and antimicrobial activity